Owner Commitment Through Internal Control and Planning to Improve the Performance of Small Companies - Wati Rosmawati; Eko Cahyo Mayndarto (Journal of Research in Business, Economics, and Education, 2020)
Planning is the process of developing and maintaining a match between the goals and capabilities of the company with the opportunities that exist and are always changing. The top management of the company which is held by the owner of the tendency is authoritarian and generally has more power than the employees in the company. The purpose of this study is to find out whether the owner of the company has a good and tight planning and control process to improve the performance of the company. The research used in this study is the type of research that will be used in this study is to explain the interrelationships between variables through hypothesis testing. This research was conducted on manufacturing companies in East Java that are still in the small and medium category and the company's top management is the factory owner. The distribution of questionnaires was carried out as many as 167 questionnaires and obtained data that can be further processed as many as 110 with a rate of 65.86%. The results of this study by processing the analysis using PLS found that the increase in owner's commitment was not able to improve good planning processes for the company but able to improve good process control for the company. The results of the analysis also show that an increase in process planning for the company has an impact on improving sustainable process control for the company as well as an impact on improving performance so as to increase competitiveness for the company.